2019
DOI: 10.3390/ijms20071677
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Expression of PD-L1

Abstract: The programmed death (PD)-1/PD-L1 pathway is a well-recognized negative immune checkpoint that results in functional inhibition of T-cells. Microglia, the brain-resident immune cells are vital for pathogen detection and initiation of neuroimmune responses. Moreover, microglial cells and astrocytes govern the activity of brain-infiltrating antiviral T-cells through upregulation of PD-L1 expression. While T-cell suppressive responses within brain are undoubtedly beneficial to the host, preventing cytotoxic damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 81 publications
0
30
0
1
Order By: Relevance
“…We have previously shown that glial cells govern the activity of brain‐infiltrating anti‐viral T‐cells via upregulation of PD‐L1 expression, likely in an effort to mitigate potentially damaging encephalitis (Schachtele, Hu, Sheng, Mutnal, & Lokensgard, 2014). Although these immunosuppressive responses are undeniably beneficial to the host, preventing damage to this vital organ, establishment of a prolonged anti‐inflammatory milieu may also result in deficiencies in viral clearance from infected brain cells (Chauhan & Lokensgard, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that glial cells govern the activity of brain‐infiltrating anti‐viral T‐cells via upregulation of PD‐L1 expression, likely in an effort to mitigate potentially damaging encephalitis (Schachtele, Hu, Sheng, Mutnal, & Lokensgard, 2014). Although these immunosuppressive responses are undeniably beneficial to the host, preventing damage to this vital organ, establishment of a prolonged anti‐inflammatory milieu may also result in deficiencies in viral clearance from infected brain cells (Chauhan & Lokensgard, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has developed an experimental murine model in which the brain becomes populated with long‐lived CD8 + T‐cells specific for immunodominant HIV‐1 Gag epitopes (Prasad, Hu, Sheng, Chauhan & Lokensgard, 2019). High numbers of activated CD8 + T‐cells against HIV antigens in the CSF of acutely infected patients have been reported (Kessing et al, 2017; Schrier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During inflammation, PDL1 expression is induced in astrocytes, oligodendrocytes [67] and endothelial cells [68] and upregulated in microglia [12] and neurons. Upregulation or induction of PDL1 in microglia and astrocytes during inflammation may limit CNS inflammation and pathology by inhibition of T cell activation [69]. In EAE, for example, responses of infiltrating PD1-expressing T cells are suppressed by microglia PDL1 expression [70].…”
Section: Immune Checkpoints In the Cnsmentioning
confidence: 99%
“…It is well known that microglial cells belong to the monocyte-macrophage system based on their source of occurrence and characteristics, showing antigen presentation function and secretion of a variety of active factors. PD-L1 is identi ed in the glial cells and expressional change is observed under CNS in ammatory state (24,25). However, it is still lack of studies on PD-1/PD-L1 working in the neurodegenerative diseases, especially relation to microglial activation and neuroin ammatory response.…”
Section: Introductionmentioning
confidence: 99%